Comparative Impact of Hospital-Based versus Non-Hospital-Based Staff Employment Models: A Focus on Clinical Trial Execution Performance - Cheng, Hui-Hsin; Liu, Ming-Che; Sung, Shian-Ying; Lin, Chih-Han; Kuo, Shu-Yu (British Journal of Healthcare and Medical Research, 2025)
Recruitment and assigning staff for the clinical study is a crucial exercise that significantly affects cost, budget, timeline, quality, and overall outcomes. Therefore, we aimed to determine the overall performance of recruited qualified hospital-hired and non-hospital hired staff in implementing clinical trial execution performance. Data were extracted from the clinical trial management system database of a teaching hospital in Taiwan. We compared the trial execution performance between hospital-hired and non-hospital-hired staff. Hospital-hired staff included clinicians, nurses, and coordinators, whereas non-hospital-hired staff were affiliated with site management organizations (SMOs) that provide professional clinical research coordinator (CRC) services. In this study, we specifically investigated rate of recruitment, screening failure, and subject’s early withdrawal between the two staffing models (hospital-Hired and non-Hospital-Hired staffing). We also found determined the association between staffing model and clinical trial distribution (Phase I-IV). Through logistic regression analysis, we identified the association between rate of recruitment, time to first subject (in days), screen failure, early withdrawal, and clinical phase distribution, with employment type. The post standardized coefficients which indicates the direction and strength of association between each predictor and outcome were also determined. Conclusively, our study revealed no significant differences for recruitment, time to first subject (in days), screen failure, early withdrawal, or clinical phase distribution between hospital-hired and non-hospital hiring models.